Meningkatkan Pengetahuan Dan Pengelolaan Keuangan Sejak Dini Melalui Gerakan “Ayo Menabung” - Falikhah, Anis Nala; Putriningsih, Saniyah; Erininda , Wafika; Adinugraha, Hendri Hermawan; Shulthoni, Muhammad (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
This service highlights the urgency of financial literacy among children in Denasri Wetan Village, facing the era of globalization. Financial literacy education is introduced early to equip children to manage finances effectively in the future. The object of service is elementary school children, especially those who attend Bimbel at Bimbel Asih in Denasri Wetan Village. The